'The Revival of the Medal': Medals, plaquettes, and the founding of Alfred Lichtwark's collection at the Hamburger Kunsthalle. (1st April 2019) - Seidel, Anna
Abstract: Alfred Lichtwark (1852–1914) was the first director (1886–1914) of the Hamburger Kunsthalle. At his personal instigation, a sculpture collection was founded. Focusing on contemporary sculpture, he became a pioneer in the museum world. Lichtwark aimed at introducing sculpture to a wider public: he considered contemporary medals and plaquettes to be the most suitable material for his purpose, and consequently he initiated the sculpture collection in 1891 by assembling ' sculptures en miniature' from Paris. In his practice he probed questions of the medals' art historical context, as well as processes of making and display. When Lichtwark published his book on the revival of the medal – Die Wiedererweckung der Medaille – in 1897, his engagement and expertise in the field were already widely respected. While he is well known as an innovative museum director, his role as collector of contemporary sculpture has not been sufficiently appreciated. This paper suggests a re- evaluation of his achievements.